Commitment and Competence as influencers of eWOM Valence. The case of Spanish accomodation in TripAdvisor. - Pérez-Aranda, Javier Ramón (My University, 2018)
The expansion of new technologies uses as a way of bringing together companies and consumers supposes multi-channel strategies in different activities or industrial sectors. Specifically, the review platforms such as TripAdvisor have changed the communication between tourist accommodation and consumers. This research, through the study of correlations, analyses the influence of commitment (training, planning and communication) and competence (productive use, active use and adoption of technology and knowledge) of accommodation with the obtained valence (much more positive than negative comments, more positive than negative comments, same positive and negative comments, more negative than positive comments and much more negative than positive comments). This research is based on a random sample of 328 Spanish accommodations with presence on TripAdvisor. With the help of Scraper software version 1.7 we obtain the comments received by the accommodation on TripAdvisor. These comments will be the foundation of the valence variable. To study the correlations between valence, commitment and competence it is used SPSS version 23. The results show a relation between commitment and valence and competence and valence. This research improves the understanding of eWOM and provides the basis for digital marketing strategies to get better reviews and ratings from customers. Future research can also investigate different company strategies as inductors of the eWOM valence.
Keywords: Marketing; Commitment; Competence; eWOM Valence